Real-Time PCR detection of Ocular Toxoplasmosis in Iraqi patients. - Issra K. Al-Aubaidi; Ali N. Yaseen; Waheeda R. Ali (Journal of Madenat Alelem University College, 2017)
Current study was done to investigate ocular toxoplasmosis that caused by Toxoplasma gondii parasite in blood samples of patients that reviewers to retina unit in Ibn- al Haitham teaching Eye hospital in Baghdad , using real-time PCR technique. Initially the disease was diagnosed by ELISA method using specific IgG and IgM antibodies for T. gondii. According to its positive results the studied groups were divided to ocular toxoplasmosis group that contain 42 patients, their proportion 84%, 14 patients in positive uveitis group in 31.1% percentage and control group recorded 35 positive case for infection with T. gondii in 41.7% percentage this group named as Asymptomatic toxoplasmosis group with significant differences (p<0.01) between the three groups. The highest mean of IgG recorded in ocular toxoplasmosis group 1.661 ± 0.187 IU/ml and also for IgM 1.922 ± 0.510 IU/ml. when Real-time PCR applied 14 positive results in ocular toxoplasmosis group were registered with 33.3 percentage against 7 positive results only for uveitis and Asymptomatic toxoplasmosis groups with rates 50% and 20% respectively without any significant differences , this test was successes in diagnosing of T.gondii parasite in different groups, although most infections were chronic with low rates in comparison with ELISA technique that recorded high rates of positive diagnosis of infection.